Curricularization of extension: a reflection on the change in undergraduate curricula - Fernandes Carvalho, Edmo; Pimenta Motta, Aline (Guará Journal, 2025)
The curricularization of University Extension is a strategy to promote citizen education in undergraduate courses, according to the guidelines of the National Education Plan (PNE 2014-2024) and CNE Resolution No. 7/2018, but as a recent proposal in undergraduate curricula it still faces challenges for its consolidation. Extension is understood as an educational, cultural and scientific process that brings university and society closer together. The research focuses on UNEB, evaluating the Political-Pedagogical Projects (PPCs) of five courses (Letters, Pedagogy, Chemistry, Mathematics and Physical Education) on different campuses. We found that all the courses comply with the requirement to include at least 10% of their workload in extension activities, albeit with different approaches. There is emphasis on practical activities and student protagonism, but there is a lack of clarity about the concrete implementation of these actions and continuity in citizen education. Exact sciences courses, such as Chemistry and Mathematics, show greater difficulty in integrating extension practices with a humanistic perspective. Although the inclusion of Extension in undergraduate curricula is necessary to contribute to a broad humanistic education, the curriculum should be complemented by curricular components focused on ethics, citizenship and social values. Authors such as Freire, Gomes and Cenci are cited to reinforce the need for an education focused on autonomy, social participation and human development, indicating that citizenship is not only built through specific actions, but with integrated and ethical training throughout the academic journey.